Monitoring small pelagic fish in the Bay of Biscay ecosystem, using indicators from an integrated survey. (September 2018) - Doray, Mathieu; Petitgas, Pierre; Huret, Martin; Duhamel, Erwan; Romagnan, Jean Baptiste; Authier, Matthieu; Dupuy, Christine; Spitz, Jérome
Highlights: A method for selecting relevant ecosystem indicators is applied to PELGAS integrated survey. River plume, bottom temperature, phyto & mesozooplankton selected as hydrobiology indicators. Small pelagic fish species appear to have followed distinct trajectories over the last 15 years. A marked decrease in mean weights of age 1 & 2 anchovy and sardine over the last 15 years is highlighted. Low impact of fishing and no effect of climate forcing on pelagic ecosystem in spring are confirmed. Abstract: This paper is a practical contribution to two important debates raised by the implementation of marine ecosystem based management: (i) which ecosystem data can be provided by a fisheries survey optimised for ecosystem monitoring; and (ii) how to combine/select potential indicators to derive useful information on marine ecosystem status and dynamics? A suite of 143 potential indicators, including spatial indices, representing small pelagic fish and their biotic and abiotic environments are presented. Indicators were routinely derived from the PELGAS integrated ecosystem survey conducted in spring in the Bay of Biscay (BoB). The general patterns over time in this suite of 5–16 years, non-stationary time series are characterised using a methodology based on min–max autocorrelation factors (MAF), to select the most continuous indicators within, and across, several ecosystem components: hydrology, phytoplankton, mesozooplankton, small pelagic fish and megafauna. Potential interactions between selected indicators and external forcing variables, including climate and fishing, were assessed. The results confirm the importance of river discharges, bottom temperature, chlorophyll-a and mesozooplankton biomass in the dynamics of the BoB pelagic ecosystem. Small pelagic fish species appear to have followed distinct trajectories during the last 15 years. A marked decrease in anchovy and sardine mean weights at ages 1 and 2 over the last 15 years was highlighted; potentially caused by density-dependent competition. The quasi-absence of significant correlation between selected survey indicators and climate and fishing pressure proxies suggests a moderate exploitation rate of small pelagic fish resources, and confirms the so far limited effects of large-scale climate forcing on the BoB pelagic ecosystem. Perspectives for the assessment of marine ecosystem status on the basis of suites of indicators derived from integrated ecosystem surveys are discussed.